2017
DOI: 10.1249/mss.0000000000001188
|View full text |Cite|
|
Sign up to set email alerts
|

Brief Intense Stair Climbing Improves Cardiorespiratory Fitness

Abstract: Brief, intense stair climbing is a practical, time-efficient strategy to improve CRF in previously untrained women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 36 publications
7
69
3
2
Order By: Relevance
“…After the 10 lb BR weight increase for the last 3 weeks both males and females increased arm ergometer VO2 max scores by an additional 9% and 11%, respectively. Overall these improvements in arm ergometer VO2 max are similar to the 5-10% improvements in leg VO2 seen following treadmill, cycle ergometer, and stair climbing HIIT (Allison et al, 2017;Astorino et al, 2012;Bayati et al, 2011;Driller et al, 2009;Laursen et al, 2005;Ziemann et al, 2011).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…After the 10 lb BR weight increase for the last 3 weeks both males and females increased arm ergometer VO2 max scores by an additional 9% and 11%, respectively. Overall these improvements in arm ergometer VO2 max are similar to the 5-10% improvements in leg VO2 seen following treadmill, cycle ergometer, and stair climbing HIIT (Allison et al, 2017;Astorino et al, 2012;Bayati et al, 2011;Driller et al, 2009;Laursen et al, 2005;Ziemann et al, 2011).…”
Section: Discussionsupporting
confidence: 55%
“…During these VO2 max tests peak HR averages were greater than 170 bpm for both baseline and after 3 weeks of BR HIIT, and above 180 bpm after 6 weeks of BR HIIT, indicating high exercising intensities at the end of the VO2 test throughout the 3 testing sessions. Additionally, we assessed As in previous HIIT treadmill, a cycle ergometry, or stair climbing protocols (Allison et al, 2017;Astorino et al, 2012;Bayati et al, 2011;Ziemann et al, 2011) and 4 weeks of BR HIIT (McAuslan, 2013), our first 3 weeks of BR HIIT 3x/week using a 30:60 sec work to rest ratio resulted in a significant 10% increase in female arm ergometer VO2 using a 20 lb BR (Figure 16). The female arm ergometer VO2 improvements after 3 weeks are similar to the 7% reported by McAuslan (2013) also using a 20 lb BR following for 4 weeks of BR HIIT.…”
Section: Discussionmentioning
confidence: 99%
“…(, ) for cycling, 18 sessions of stair climbing over 6 weeks increased V̇O2normalpeak by 12%, which corresponded to approximately 1 metabolic equivalent (MET) (Allison et al . ). Phillips et al .…”
Section: Introductionmentioning
confidence: 97%
“…Allison et al . () reported that mean heart rate and RPE were similar when previously sedentary young women performed an acute session of either cycling or stair climbing, using a 10 min protocol that involves 3 × 20 s sprints. Similar to the results reported by Gillen et al .…”
Section: Introductionmentioning
confidence: 99%
“…The VO 2peak corresponded to the highest value achieved over a 30 second period. To determine if a valid maximal effort was achieved during the VO 2peak test, participants were required to meet two out of four of the following criteria: HR max within 10 bpm of their predicted maximum, respiratory exchange ratio > 1.1, plateau, and/or volitional exhaustion [33]. All participants exerted maximal effort according to these criteria.…”
Section: Experimental Designmentioning
confidence: 99%